Empirical Study Of The Impact Of Presence And Para Social Presence On Trust In Online Virtual Electronic Commerce - Teoh, Kung Keat (2008)
This study analyzes users' acceptance of such online immersive virtual malls and gauges the impact of these malls on acceptance, user trust, and intended use in an empirical manner using quantitative approachers.